Atmospheric aerosol at the Svalbard Islands in year 2010. Modal structure, elemental composition and time dependence of the crustal aerosol component - MITTNER P; CECCATO D; SARTORI P; MASIOL M; PAVONI B; VITALE V; LUPI A; BUSETTO M; BECAGLI S; UDISTI R (AIP Conference Proceedings,, 2013)
A multiannual multipurpose experiment on atmospheric properties is being carried on at the Svalbard Islands, starting in year 2010. Major reasons of interest, both climatic and chemical, concerning the study of atmospheric aerosol, together with basic experimental features will be presented. Detailed results being presented concern 40 size-segregated aerosol samples collected in year 2010 (4 days sampling time) with a 12-stage SDI impactor and PIXE analyzed. Elemental Mass Size Distributions are fitted with lognormal functions. Up to three size modes (super-and sub-micrometric; intermediate) are determined for each element. Emphasis is given to the crustal aerosol component, due its crucial climatic rôle. Position, width and intensity of each mode of element Si are displayed, together with the ratios of the concentration of Al, Fe, Ti Mn (and possibly other elements) vs. Si, in the supermicrometric mode. These data will be used for singling out the major crustal components and helping determining their origin and their interaction with radiation. © 2013 AIP Publishing LLC.